DINAMIKA PENDIDIKAN MUHAMMADIYAH - Pasmah chandra (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2018)
Muhammadiyah education (Muhammadiyah school) is currently entering the era of competition. Muhammadiyah education must modernize education management. Modernization in the development of Muhammadiyah school management can be done on aspects of curriculum management, management of educators and education, student management and management of facilities and infrastructure. But on the other hand, Muhammadiyah schools are not enough to just develop in the field of school management. Muhammadiyah schools must maintain the existence of Ahmad Dahlan's noble values ​​as spirits from Muhammadiyah schools. Do not let Muhammadiyah schools only have the Muhammadiyah